2023
DOI: 10.12938/bmfh.2022-005
|View full text |Cite
|
Sign up to set email alerts
|

Camellia oil (<i>Camellia oleifera</i> Abel.) treatment improves high-fat diet-induced atherosclerosis in apolipoprotein E (ApoE)<sup>−/−</sup> mice

Abstract: Atherosclerosis is the main cause of cardiovascular diseases, and healthy dietary habits are a feasible strategy to prevent atherosclerosis development. Camellia oil, an edible plant oil, exhibits multiple beneficial cardiovascular effects. Our previous study showed that oral administration of camellia oil attenuated hyperglycemia, fat deposits in the liver, and the atherosclerosis index in high-fat diet (HFD)-induced obese mice.Here, an atherosclerosis model of apolipoprotein E (ApoE) -/mice induced by HFD wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…For hepatic biochemical analysis, the right lobe of liver tissues (10 mg) was homogenized in 90 μL of saline at 65 Hz at 4°C for 2 min using a magnetic bead homogenizer (Jinxin Industrial Development Co., Ltd., Shanghai, China). The homogenate was then centrifuged at 3000× g at 4°C for 10 min, as previously described (Huang et al., 2023 ). The supernatant was collected, and the protein concentration was measured using a BCA protein assay kit.…”
Section: Methodsmentioning
confidence: 99%
“…For hepatic biochemical analysis, the right lobe of liver tissues (10 mg) was homogenized in 90 μL of saline at 65 Hz at 4°C for 2 min using a magnetic bead homogenizer (Jinxin Industrial Development Co., Ltd., Shanghai, China). The homogenate was then centrifuged at 3000× g at 4°C for 10 min, as previously described (Huang et al., 2023 ). The supernatant was collected, and the protein concentration was measured using a BCA protein assay kit.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that consuming Camellia oleifera oil can reduce the risk factors associated with cardiovascular disease ( Fig. 6 ) ( Huang et al, 2023 ).…”
Section: Biological Function Of Camellia Oleifera Oilmentioning
confidence: 99%
“…oleifera saponins (CoS) . These CoS, occurring naturally as non-ionic surfactants, are present in various parts of camellia plants, including roots, stems, leaves, flowers, and seeds. , Although husks and pomace from camellia seeds are often used in low-value commodities, such as hair shampoos, insecticides, and other items, their frequent disposal leads to substantial resource inefficiencies. , These waste materials encompass chemical constituents, such as saponins and flavonoids. Of particular significance, CoS, which exhibit a structural resemblance to pentacyclic triterpenoids and comprise sapogenins, glycosides, and organic acids, hold particular significance.…”
Section: Introductionmentioning
confidence: 99%